Unitended consequences: Western soft power as a source of legitimacy for Central Asian autocrats - Andrea Schmitz; Esther Somfalvy (Stiftung Wissenschaft und Politik (SWP), 2011)
The policy of the EU and its member states vis-à-vis Central Asia's authoritarian states is focused first and foremost on stability. At the same time, it is hoped that the region's political elites will allow themselves to be swayed by 'constructive engagement' and 'dialogue' to abide by human rights standards and to pursue democratic reforms. In accordance with this policy, the Central Asian states are incorporated into international cooperation projects, which focus on shared interests and blur the variance in different values. Just how unsuccessful this approach is has been demonstrated by Kazakhstan's OSCE chairmanship. Kazakhstan's leadership has primarily used the office to consolidate its domestic power rather than promoting acceptance of the 'human dimension' of security in the post-Soviet space and leading by good example. If it wishes to avoid such outcomes in the future, the West must develop a more acute awareness of the behavioural logic driving its partners
Keywords: 320